PENGARUH BRAND IMAGE DAN BRAND LOVE TERHADAP PURCHASE DECISION MELALUI WORD OF MOUTH (Pada pengguna Oppo Smartphone di Mbah Jo Malang) - Ana Laillaturovikoh; N Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT               This study aims to determine the effect of brand image and brand love on purchase decision through word of mouth in Oppo Smartphone users in Mbah Jo Malang. The population in this study took from data obtained from users of Oppo Smartphone Mbah Jo Malang in February-April. Sampling in this study was 93 respondents. The analytical method used is the path analysis method. The results in this study indicate that the significant t-test on the brand image variable (X1) 0.000 with t-count is 3.957 smaller than the value of α (0.05) this means that brand image (X1) has a significant positive effect on word of mouth (Z). On the significant value of t-test on the brand image variable (X2) 0,000 with t-count is 8.723 smaller than the value of α (0.05) this means that brand love (X2) is positive for word of mouth (Z). significant t-test on brand image variable (X1) 0.045 with t count is 2,030 smaller than α (0,05) this means that brand image (X1) has a significant positive effect on purchase decision (Y). On the significant value of t-test on the variable brand love (X2) 0.000 with t-count is 5.602 smaller than the value of α (0.05) this means that brand love (X2) is positive for purchase decision (Y). the significant value of t-test on the purchase decision variable (Y) 0,000 with t-count is 8.257 which is smaller than the value of α (0.05) this means that word of mouth (Z) has a significant positive effect on purchase decision (Y).  Keyword: Brand Image, brand Love , Purchase Decision, Word Of Mouth